2011
DOI: 10.1538/expanim.60.133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intestinal Microflora on Superoxide Dismutase Activity in the Mouse Cecum

Abstract: Abstract:In the antioxidant defense system, superoxide dismutase (SOD) catalyzes the breakdown of superoxide into hydrogen peroxide and oxygen. In the cecum, the influence of intestinal microflora on SOD activity is unknown. In this study, we used germ-free (GF) mice to examine the effect of intestinal microflora on SOD activity in the cecum, and SOD activity was compared between GF and conventional (CV) mice. The activity of CuZnSOD and MnSOD was determined using the SOD Assay Kit-WST. Expressions of CuZnSOD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…These findings are in agreement with the results of our previous report in the whole cecal body [7]. Furthermore, we previously reported that the total SOD activity in the ceca of CVz mice was significantly lower than in the ceca of GF mice [7]. In addition, we confirmed that total SOD activity in the cecal mucosa of pseudo-GF mice treated with antibiotics in CV mice (1,500 U/ml penicillin-G and 2 mg/ml streptomycin sulfate for 4 days) was significantly higher than that of CV mice (data not shown), although it was a preliminary study.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…These findings are in agreement with the results of our previous report in the whole cecal body [7]. Furthermore, we previously reported that the total SOD activity in the ceca of CVz mice was significantly lower than in the ceca of GF mice [7]. In addition, we confirmed that total SOD activity in the cecal mucosa of pseudo-GF mice treated with antibiotics in CV mice (1,500 U/ml penicillin-G and 2 mg/ml streptomycin sulfate for 4 days) was significantly higher than that of CV mice (data not shown), although it was a preliminary study.…”
Section: Discussionsupporting
confidence: 94%
“…We also found that CuZnSOD mRNA expression showed similar tendencies with respect to SOD activities in the intestinal mucosa. These findings are in agreement with the results of our previous report in the whole cecal body [7]. Furthermore, we previously reported that the total SOD activity in the ceca of CVz mice was significantly lower than in the ceca of GF mice [7].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations